2009
DOI: 10.1021/bi900982t
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Peptides That Target the Aminoacyl-tRNA Site of Bacterial 16S Ribosomal RNA

Abstract: For almost five decades, antibiotics have been used successfully to control infectious diseases caused by bacterial pathogens. More recently, however, two-thirds of bacterial pathogens exhibit resistance and are continually evolving new resistance mechanisms against almost every clinically used antibiotic. Novel efforts are required for the development of new drugs or drug leads to combat these infectious diseases. A number of antibiotics target the bacterial aminoacyl-tRNA site (A site) of 16S ribosomal RNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
(97 reference statements)
0
29
0
Order By: Relevance
“…We previously showed that NCL utilizes its RRM domains to interact with expanded-CAG RNA ( Tsoi et al, 2012 ). We next tested whether P3, which is derived from NCL's RRM2, interacts physically with expanded-CAG RNA, by using isothermal titration calorimetry (iTC) ( Li et al, 2009 ; Wong et al, 2014 ). We first showed that the synthetic wild-type P3 peptide associated with unexpanded MJD CAG27 RNA with a K D value of 127.60±26.88 µM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that NCL utilizes its RRM domains to interact with expanded-CAG RNA ( Tsoi et al, 2012 ). We next tested whether P3, which is derived from NCL's RRM2, interacts physically with expanded-CAG RNA, by using isothermal titration calorimetry (iTC) ( Li et al, 2009 ; Wong et al, 2014 ). We first showed that the synthetic wild-type P3 peptide associated with unexpanded MJD CAG27 RNA with a K D value of 127.60±26.88 µM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study described phage display selection of peptides binding to the ribosomal A-site RNA [91]. Hexapeptides were identified with detectable in vitro translation activity, though potency was weaker than that of natural product aminoglycosides.…”
Section: Strategies For Identifying Rna-binding Ligandsmentioning
confidence: 99%
“…Recently, phage display technology has allowed us to find selective peptide(s) against RNA of interest by screening a peptide library of around 10 9 or more complexity ( 37 , 38 ). We have used phage display against pre-miR-21 to find out a selective peptide that binds to pre-miR-21 and block Dicer processing and thereby downregulate miR-21 expression.…”
Section: Introductionmentioning
confidence: 99%